Promoting Sustainable Mobility by Addressing Inequities in Electric Bike-Sharing Systems - M. Mavin De Silva; S. W. Y. B. Pavithra K. Baddewela; T. Sivakumar; Tadachika Nakayama (Journal of South Asian Logistics and Transport)
Transition to electric bike-sharing systems (EBSS) offers a sustainable and efficient solution for urban mobility, reducing emissions and enhancing accessibility. This study used data from New York City's bike-sharing program, combining socio-demographic factors, built environment indicators, and bike station placement insights to assess EBSS adoption. Using participatory system dynamics modelling, we developed causal loop diagrams to compare the dynamics of cycling adoption in two contrasting contexts: New York, USA, where EBSS is well-integrated as a last-mile and supplementary transportation mode, and Colombo, Sri Lanka, where e-bike adoption remains limited. Key feedback loops identified in New York emphasise the role of infrastructure investments, public transit integration, and safety measures in driving EBSS demand. These insights were adapted to Colombo, revealing potential strategies such as improving cycling infrastructure, integrating EBSS with transit systems, and launching awareness campaigns to overcome cultural and behavioural barriers. The findings provide a systematic framework for policymakers, urban planners, and stakeholders to accelerate EBSS adoption in diverse urban settings. By applying lessons from New York to Colombo, this study highlights actionable pathways to foster e-bike culture and sustainable urban mobility.